Priorities in health: what do they mean to Brazilian adults? - Felipe Fossati Reichert; Marlos Rodrigues Domingues; Pedro C. Hallal; Mario Renato Azevedo; Fernando Vinholes Siqueira; Aluísio J.D. Barros
We aimed to evaluate how Brazilian adults rank seven well-known health-related factors in terms of importance for health. A population-based study was undertaken in Pelotas, Rio Grande do Sul State, Brazil (N = 3,100; response rate: 96.5%). Individuals ranked three out of seven factors that, in their opinion, were the most important for health. The factors investigated were: "controlling stress", "practicing physical activity regularly", "avoiding drinking in excess", "avoiding smoking", "visiting a doctor regularly", "keeping the ideal weight", and "having a healthy diet". Healthy diet (73.9%), physical activity (59.9%), and visiting a doctor regularly (45.7%) were the most frequently reported factors. Younger subjects and those with higher socioeconomic status were more likely to report physical activity and stress as important factors for health than their counterparts. The importance attributed to health-related factors changes markedly among population subgroups.